Odpowiedzi

2010-04-07T21:18:06+02:00
1) 2x-9= 7+x
2x-x=7+9
x=16

2) 2(1-x)=-3x-61+4x
2-2x=-3x-61+4x
-2x+3x-4x=-61-2
-3x=-63 /:(-3)
x=21

3) 2x-5(0,2x-5)=3(x-5)-20
2x-x+25=3x-15-20
2x-x-3x=-15-20-25
-2x=-60 /:(-2)
x=30

4) 2x+3(22-x)=x-3(8-x)
2x+66-3x=x-24+3x
2x-3x-x-3x=-24-66
-5x=-90 /:(-5)
x=18

5) 2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x=3x-42-7x-5
2x-9x-3x+7x=-42-5+2+3
-3x=-42 /:(-3)
x=14
2010-04-07T21:32:41+02:00
Zaczne od 2 podpunktu
2(1-x)=-3x-61+4x
2-2x=x-61|-2
-2x=x+63|-x
3x=63|:3
x=21

2x-5(0,2x-5)=3(x-5)-20
2x-x+25=3x-15-20
x+25=3x+35|-25
x=3x+10|-3x
2x=10|:2
x=5

2x+3(22-x)=x-3(8-x)
2x+66-3x=x-24+3x
-x+66=4x-24|-66
-x=4x+90|-4x
5x=90|:5
x=18

2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x=3x-42-7x-5
-7x+5=-4x+47|-5
-7x=-4x+42|+4x
-3x=42|:(-3)
x=14
Najlepsza Odpowiedź!
2010-04-07T21:39:14+02:00
Z.63
2z-9= 7+x ( z czy x?? stawiam na x :-)
2x-9= 7+x
2x-x = 7+9
x = 16

2(1-x)=-3x-61+4x
2-2x = -3x-61+4x
-2x-4x+3x = -61-2
-3x = -63 |:(-3)
x = 21

2x-5(0,2x-5)=3(x-5)-20
2x-x+25 = 3x-15-20
x-3x = -35-25
-2x = -60 |:(-2)
x = 30

2x+3(22-x)=x-3(8-x)
2x+66-3x = x-24+3x
2x-3x-x-3x = -24-66
-5x = -90 |:(-5)
x = 18

2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x = 3x-42-7x-5
2x-9x-3x+7x = -42-5+5
-3x = -42 |:(-3)
x = 14

z.62
2/3x+3 1/2 = 4,3
2/3x = 4,3-3,5
2/3x = 0,8
x = 1,2

7/3+10/9x = 22/9
10/9x = 22/9 -7/3
10/9x = 1/9
x = 0,1

28/5 = 4,6+0,5x
-0,5x = -28/5+4,6
-0,5x = -1 |:(-0,5)
x = 2

10x-3,75 = 61/4
10x = 61/4+3,75
10x = 19
x = 1,9

5x-4,6 = 0,9
5x = 0,9+4,6
5x = 5,5
x = 11/10
x = 1,1

0 = 3x-0,9
-3x = -0,9
x = 0,3

3/8 = 5/2x-0,125
-5/2x = -0,125-3/8
-5/2 x =- 500/1000
-5/2 x = -0,5
x = 0,2

x/3-1/4 = 0,45 |*12
4x-3 = 5,4
4x = 5,4+3
4x = 8,4
x = 2,1

2,78-x = 1,78
-x = 1,78-2,78
-x = -1
x = 1